Establishing content validity of an orthodontic subset of the FACE‐Q Craniofacial Module in children and young adults with malocclusion. (15th March 2021) - Tassi, Ali; Tan, Jessica; Piplani, Bhoomika; Longmire, Natasha; Wong Riff, Karen W. Y.; Klassen, Anne F.
Abstract: Objective: The FACE‐Q Craniofacial Module for children and young adults is a patient‐reported outcome measure (PROM) designed to measure outcomes for patients aged 8 to 29 years with facial conditions. The aim of this study was to establish content validity of a relevant subset of the module for its use in orthodontic patients with malocclusion. Setting and Sample Population: Experts in orthodontics were emailed and invited to provide feedback through a Research Electronic Data Capture survey. Patient feedback was obtained through cognitive interviews with patients aged 8 to 29 years recruited from a university‐based orthodontic clinic in Canada. Materials and Methods: Expert opinion and patient interviews were used to obtain feedback on the content of 4 appearance (face, smile, teeth and jaws) and 1 function (eating and drinking) scales hypothesized to be relevant to orthodontic malocclusions, and to elicit new concepts. Interviews were audio‐recorded, transcribed, and coded using a line‐by‐line approach. Results: Twenty‐one experts and 15 patients participated. Expert feedback led us to drop 9, retain 40, revise 4 and add 16 new items. At the conclusion of cognitive interviews no items were dropped, 55 were retained, 5 were revised and 8 new items were added. The final set of 68 items demonstrated content validity for orthodontic patients. Conclusion: Expert feedback and cognitive interviews enabled us to revise and refine 5 scales as part of the FACE‐Q Craniofacial Module for use in orthodontic patients. These scales were included in the internationalfield‐test of the FACE‐Q Craniofacial Module.